PENGARUH LATIHAN KEKUATAN OTOT LENGAN TERHADAP PENINGKATAN KEMAMPUAN SHOOTING THREE POINT PADA ATLIT BASKET EKSTRAKURIKULER SMA NEGERI 1 GEBANG - Kurniawan, Rizkei; Syahputra, M. Yoga; Akbari, Myrza; Rangkuti, Yoki Afriandi; Cahyadi, Agung (Dharmas Journal of Sport, 2024)
The background to the problem of this research is the weak three-point shooting ability of extracurricular basketball athletes at SMA Negeri 1 Gebang, making it difficult to get three points directly when competing. The aim to be achieved in this research is to determine the increase in three-point shooting ability in extracurricular basketball athletes at SMA Negeri 1 Gebang. The method used in this research is experimentation with a research design, namely preetest-posttest design. The instrument in the research is three point shooting. Data was taken from the initial test (pretest) and final test (posttest). The treatment in the study consisted of training using weights given for 16 meetings with a training frequency of 3 times a week. The data analysis technique uses the SPSS Statistics version 23 application, measurement and testing of results uses the data normality test, data homogeneity test, t statistical test. Research results obtained t value = 23,000 > 1,812, so "Ho is rejected". Conclusion: that there is an influence of arm muscle strength training on increasing three-point shooting ability in extracurricular basketball athletes at SMA Negeri 1 Gebang. From the results of the discussion above, it can be concluded that arm muscle strength training can provide positive results on the three-point shooting ability of extracurricular basketball athletes at SMA Negeri 1 Gebang, whose three-point shooting ability was previously still weak, but has now become better after being given arm muscle strength training.